Short Communication: Distribution of dragonflies (Odonata: Insecta) in South Ural lakes, Russia - IRINA V. MASHKOVA; TATYANA G. KRUPNOVA; ANASTASIYA M. KOSTRYUKOVA; NIKITA E. VLASOV (Biodiversitas Journal of Biological Diversity, 2018)
Mashkova IV, Krupnova TG, Kostryukova AM, Vlasov NE. 2018. Short Communication: Distribution of dragonflies (Odonata: Insecta) in South Ural lakes, Russia. Biodiversitas 19: 202-207. This paper studies the diversity and distribution of Odonata (Insecta) in the South Urals region lakes such as Lake Large Miassovo, Lake Small Miassovo, Lake Ilmenskoe, Lake Savelkul and Lake Baraus. We revised dragonflies in five lakes during May-September 2014-2016. Dragonflies and larvae were identified up to the species. As results, 36 species (12 Zygoptera and 22 Anisoptera) belonging to 15 genera were recorded. To compare the similarities of dragonfly communities of different lakes we used the Canonical Correspondence Analysis (CCA) according the Jaccard index. Comparing the number of records of odonate species for selected lakes in our study, we found that the small richness of species was typical for lakes Savelkul and Baraus (22% and 25% of the total number of species, respectively) and the large values of the species richness was obtained for lakes Small Miassovo, Ilmenskoe and Large Miassovo (50%, 72%% and 80% of the total number of species, respectively).